2017
DOI: 10.14687/jhs.v14i4.4729
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of orthorexic tendencies with eating attitude and obsessive compulsive symptoms<p>Ortorektik eğilimlerin yeme tutumu ve obsesif kompulsif belirtilerle ilişkisi

Abstract: Aim: The object of the study is to determine the relationship of orthorexic tendencies with the eating attitude and obsessive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…The study by Dell’Osso included a sample of 2826 individuals with a percentage of 40.6% women and 60% men, and found significant differences, revealing a greater tendency for orthorexia in women compared to men [ 40 ]. In contrast, other studies have shown higher prevalence rates in men compared to women [ 25 , 38 , 42 ]. In a sample of 878 medical students, Fidan et al [ 25 ] found a greater tendency towards ON behavior, in males, using the Turkish validation of ORTO-15.…”
Section: Discussionmentioning
confidence: 72%
“…The study by Dell’Osso included a sample of 2826 individuals with a percentage of 40.6% women and 60% men, and found significant differences, revealing a greater tendency for orthorexia in women compared to men [ 40 ]. In contrast, other studies have shown higher prevalence rates in men compared to women [ 25 , 38 , 42 ]. In a sample of 878 medical students, Fidan et al [ 25 ] found a greater tendency towards ON behavior, in males, using the Turkish validation of ORTO-15.…”
Section: Discussionmentioning
confidence: 72%
“…First, the research gives insight to understand the behaviors of foreign residents. In previous studies, eating attitude was generally associated with health, eating disorders, family environment, and obesity (Aikman et al, 2006;Çulhacık & Durat, 2017;Tunç, 2019). In this study, three eating behaviors, emerged from the theories of the Psychosomatics, Externality and Restrained, were examined in the context of the foreign residents' attitudes toward a culinary culture.…”
Section: Conceptual Contributionmentioning
confidence: 96%
“…Çalışmamızda ON ile cinsiyet arasında istatistiksel olarak anlamlı bir fark bulunmadı (p>0,05) (Tablo 6). Ulus ve Taşçı'nın (30) (17,20,45). Dalmaz ve Yurtdaş da (46) ON ile ilgili çalışmalarını planlarken kadınları ON açısından risk grubu olarak gördükleri için sadece onları örneklem popülasyonuna almışlardır (46).…”
Section: Introductionunclassified